Digitalisasi Desa: Pemberdayaan Ekonomi Lokal di Kecamatan Bokat Kabupaten Buol - Olii, Salahudin; Aneta, Yanti; Zakaria, Alfian; Ahaliki, Budiyanto; A., Hermila (Universitas Negeri Gorontalo, 2024)
In 1999 the Buol area became a district which was a division of the Buol-Toli-Toli district, the Buol district was split based on Law no. 51 of 1999, and ratified on September 16, 1999 and inaugurated on November 27, 1999, on behalf of the Minister of Home Affairs, namely Governor H.B Paliuju. Abdul Karim Mbouw was inaugurated in Jakarta as the first acting Buol district head on 12 October 1999. Buol District has 11 sub-districts and 115 Villages/Kelurahan. The territory of Buol Regency consists of a land area with a land area of 4,043.57 km2. One of the sub- districts in Buol district is Bokat sub-district. Bokat District has the potential for Marine Economy and plantations which are a source of income for the community. The marine potential has a tourist attraction and an abundant variety of fish, while the potential for plantation agriculture is in the form of copra, cloves, durian, nutmeg and other seasonal crops. The economic activities that have been carried out by the Bokat community so far in uncovering the potentials that still exist in traditional patterns, the use of technology has not been used. One of the applications of ICT is the creation of a village website which includes related tourism potential and agricultural and plantation potential. Management of village administration and sub-district administrative area violations. Therefore, ICT can be a solution to the problem of accessing various sources of information that are affordable, relevant and reliable by business actors in increasing economic potential (Madukwe 2006). By conducting training and mentoring programs on the application of ICT to the coastal communities of Tomini Bay, especially in the Bokat sub-district, Buol district, it is hoped that it will be able to boost the economy of the local community. Thematic KKN which raises the title of developing information technology towards Digital Village is a solution in the era of technological development and being able to compete for the industrial economy 4.0Keywords: TIK; Buol; Digital Village. AbstrakPada tahun 1999 wilayah buol menjadi kabupaten yang merupakan pemekaran dari kabupaten buol-toli-toli, kabupaten buol dimekarkan berdasarkan Undang undang No. 51 tahun 1999, dan disahkan pada tanggal 16 september tahun 1999 dan diresmikan pada tanggal 27 november tahun 1999, atas nama Mentri Dalam Negeri yaitu Gubernur H.B Paliudju. Abdul Karim Mbouw dilantik di jakarta sebagai pejabat bupati Buol pertama pada tanggal 12 oktober tahun 1999. Kabupaten Buol memiliki 11 kecamatan dan 115 Desa/Kelurahan. Wilayah Kabupaten Buol terdiri atas wilayah daratan dengan luas wilayah daratan 4.043,57 km2. Salah satu Kecamatan yang ada di kabupaten Buol yaitu Kecamatan Bokat. Kecamatan Bokat memiliki potensi Ekonomi Kelautan dan pertanian perkebunan yang menjadi sumber pendapatan bagi masyarakat. Potensi laut memiliki daya tarik wisata dan ragam ikan yang berlimpah, sedangkan potensi pertanian perkebunan berupa tanaman kopra, cengkeh, durian, buah pala dan tanaman musiman lainnya. Kegiatan ekonomi yang dilakukan selama ini oleh masyarakat Bokat dalam mengekspos potensi-potensi yang ada masih pada pola traditional, penggunaan teknologi belum digunakan. Salah satu penerapan TIK adalah pembuatan website desa yang didalamnya memuat terkait potensi pariwisata dan potensi pertanian, perkebunan. Pengelolaan administrasi desa dan pemetaan wilayah administrasi kecamatan. Oleh karena itu TIK dapat menjadi solusi untuk masalah mengakses berbagai sumber informasi yang terjangkau, relevan, dan dapat diandalkan oleh para pelaku usaha dalam meningkatkan potensi ekonomi (Madukwe 2006). Dengan melakukan program pelatihan dan pendampingan terhadap penerapan TIK kepada masyarakat pesisir teluk tomini khususnya dikecamatan Bokat kabupaten Buol diharapkan mampu mendorong perekonomian Masyarakat setempat. KKN Tematik yang mengangkat judul pengembangan teknologi informasi menuju Desa Digital menjadi solusi dalam perkembangan era teknologi dan mampu bersaing dibidang perekonomian industri 4.0.Kata Kunci: TIK; Buol; Desa Digital.